GLOBAL MARKETING DECISION (KEPUTUSAN PEMASARAN) - Azzahra Nst, Annisaa Putri; Ananda, Fitri Tia; Indahsari, Lily Nur; Suhairi, Suhairi (Universitas Labuhanbatu, 2021)
This paper aims to study the understanding of decision-making to enter global marketing and approach decisions through global marketing strategies that are scientifically and practically applicable for Indonesian companies in the face of today's competitive globalization. The results of this study will provide results both in the literature and practically on the application of the two decision approaches through the global marketing strategy. So that it is expected to be able to contribute to Indonesian companies in making decisions through global marketing strategies so that Indonesian companies can excel in the competition of globalization.